1980
DOI: 10.1007/bf00276400
|View full text |Cite
|
Sign up to set email alerts
|

Changes in growth, appetite, food conversion efficiency and body composition in mice selected for high post-weaning weight gain on restricted feeding

Abstract: This study aimed to test the hypothesis that if animals were fed the same amount over the same time period, selection of the fastest growers would result in a change in the partitioning of metabolisable energy toward more protein and less fat deposition. Two mouse lines (S1 and S2) were selected for high 5 to 9 week weight gain corrected to mean 5 week weight. Appetite variation between mice was eliminated by feeding a fixed amount to each mouse daily. After 6 generations of selection, the lines were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…For example, artificial selection for an increase in growth rate (i.e. production) is often accompanied by a decrease in the cost of maintenance metabolism as has been reported for rats (Getty, Mills & Henricks, 1988), mice (Kownacki et al, 1975;Kownacki & Keller, 1978;McPhee et al, 1980;Roberts, 1981;Malik, 1984;Urrutia & Hayes, 1988), and chickens (Pym & Farrell, 1977). This result is more chacteristic of experimental designs that limit consumption during selection for high production.…”
Section: Discussionmentioning
confidence: 87%
“…For example, artificial selection for an increase in growth rate (i.e. production) is often accompanied by a decrease in the cost of maintenance metabolism as has been reported for rats (Getty, Mills & Henricks, 1988), mice (Kownacki et al, 1975;Kownacki & Keller, 1978;McPhee et al, 1980;Roberts, 1981;Malik, 1984;Urrutia & Hayes, 1988), and chickens (Pym & Farrell, 1977). This result is more chacteristic of experimental designs that limit consumption during selection for high production.…”
Section: Discussionmentioning
confidence: 87%
“…Dalton (1967), McPhee et al (1980) andYtiksel et al (1981) working with mice and Bailey et al (1970) working with rats found no genotype-environment interactions. The reason for the lack of interaction in the study of Yiiksel et al (1981) may be that they selected for efficiency instead of gain or weight as in most studies.…”
Section: (Ii) Direct and Correlated Responsesmentioning
confidence: 97%
“…for GR and F respectively. In mouse lines selected for increased body-weight gain on a fixed feeding scale, McPhee, Trappett, Neill and Duncalfe (1980), Hetzel and Nicholas (1986) and McPhee and Trappett (1987) attributed the response to a reduction in the energy used for maintenance and, to a lesser degree, an improvement in the use of retained energy through an increased lean and reduced fat deposition. respectively.…”
Section: Selection Processmentioning
confidence: 99%